TGF-β in fibrosis by acting as a conductor for contractile properties of myofibroblasts - Alexandre Vallée; Yves Lecarpentier (Cell & Bioscience, 2019)
Abstract Myofibroblasts are non-muscle contractile cells that play a key physiologically role in organs such as the stem villi of the human placenta during physiological pregnancy. They are able to contract and relax in response to changes in the volume of the intervillous chamber. Myofibroblasts have also been observed in several diseases and are involved in wound healing and the fibrotic processes affecting several organs, such as the liver, lungs, kidneys and heart. During the fibrotic process, tissue retraction rather than contraction is correlated with collagen synthesis in the extracellular matrix, leading to irreversible fibrosis and, finally, apoptosis of myofibroblasts. The molecular motor of myofibroblasts is the non-muscle type IIA and B myosin (NMMIIA and NMMIIB). Fibroblast differentiation into myofibroblasts is largely governed by the transforming growth factor-β1 (TGF-β1). This system controls the canonical WNT/β-catenin pathway in a positive manner, and PPARγ in a negative manner. The WNT/β-catenin pathway promotes fibrosis, while PPARγ prevents it. This review focuses on the contractile properties of myofibroblasts and the conductor, TGF-β1, which together control the opposing interplay between PPARγ and the canonical WNT/β-catenin pathway.